1998
DOI: 10.1152/ajprenal.1998.274.3.f445
|View full text |Cite
|
Sign up to set email alerts
|

Model explaining the relation between distal nephron Li+ reabsorption and urinary Na+ excretion in rats

Abstract: Li+ may be reabsorbed via an amiloride-sensitive mechanism in the collecting ducts of rats administered a low-Na+ diet. This was investigated by measuring the increase in fractional urinary excretion of Li+(FELi) in response to amiloride in conscious rats at two different levels of plasma Li+ concentration and after administration of bendroflumethiazide (BFTZ), angiotensin III (ANG III), and aldosterone (Aldo). The results confirmed that amiloride increased (FELi) in rats on a low-Na+ diet (20 ± 1 to 35 ± 1%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 14 publications
6
21
0
Order By: Relevance
“…Rats in the present work excreted amiloride at a rate of ϳ1.1 nmol⅐min Ϫ1 ⅐100 g body wt Ϫ1 , on the same order as that of Shalmi and coworkers (33), who estimated that the concentration of amiloride in the proximal tubules was well below that reported to block the Na ϩ /H ϩ exchange mechanism on the proximal tubule (the inhibitory constant, K i Ͼ50 -100 mol) but, at ϳ100 mol/l in the collecting duct, well above that needed to prevent movement of sodium through the epithelial sodium channel (K i Ͻ1 mol/l) (4). At these concentrations, Thomsen and others (38) found that amiloride also inhibited lithium and sodium reab- sorption in the proximal tubules of conscious rats and suggested that the reason such a dose of amiloride showed no effect on sodium reabsorption by the proximal tubule in micropuncture studies was due to the activation of sodiumretaining mechanisms by acute anesthesia or surgery (39).…”
Section: Discussionsupporting
confidence: 76%
“…Rats in the present work excreted amiloride at a rate of ϳ1.1 nmol⅐min Ϫ1 ⅐100 g body wt Ϫ1 , on the same order as that of Shalmi and coworkers (33), who estimated that the concentration of amiloride in the proximal tubules was well below that reported to block the Na ϩ /H ϩ exchange mechanism on the proximal tubule (the inhibitory constant, K i Ͼ50 -100 mol) but, at ϳ100 mol/l in the collecting duct, well above that needed to prevent movement of sodium through the epithelial sodium channel (K i Ͻ1 mol/l) (4). At these concentrations, Thomsen and others (38) found that amiloride also inhibited lithium and sodium reab- sorption in the proximal tubules of conscious rats and suggested that the reason such a dose of amiloride showed no effect on sodium reabsorption by the proximal tubule in micropuncture studies was due to the activation of sodiumretaining mechanisms by acute anesthesia or surgery (39).…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have shown that amiloridesensitive Li reabsorption takes place only in the distal nephron during conditions with Na depletion (low-Na diet). 12,24 In this study, we showed that Li-treated mice receiving a normal Nacontaining diet develop NDI and that the absence of ENaC in the CD prevents the development of NDI. Thus, we show that ENaC-mediated Li reabsorption does occur in the CD in mice on a normal-salt diet.…”
Section: Enac-mediated LI Entrymentioning
confidence: 59%
“…9,10 Moreover, amiloride, a specific blocker of ENaC, has been shown to reduce Li uptake in ENaC-expressing renal cells 11 and to block reabsorption in the distal nephron of Na-depleted rats. 12 Recent studies also showed that amiloride partially prevents development of Li-NDI in rats 11,13 and partially restores the urine-concentrating ability in patients who are on Li therapy. 14 To provide possibly definitive proof of whether ENaC is involved in the absorption of Li, we took advantage of transgenic mice deficient of ␣ENaC specifically in the CD while leaving ENaC expression in the late DCT and CNT intact.…”
mentioning
confidence: 99%
“…A key finding is that Li þ reabsorption in the distal nephron is blocked by amiloride [2][3][4][5][6][7][8], which inhibits the conductive epithelial Na þ channel (ENaC) present in the apical membrane. Therefore, it is highly likely that Li þ reabsorption in the distal nephron uses this transporter rather than any of the others.…”
Section: Apical Membranementioning
confidence: 99%
“…This is the basis for the use of Li þ clearance as an index of proximal tubular fluid output [1]. Surprisingly, however, when rats are given a diet that is low in either Na þ or K þ , substantial Li þ reabsorption does take place in the distal nephron [2][3][4][5][6][7][8][9]. The present article will address this remarkable lability of distal Li þ transport, in an attempt not only to understand Li þ handling itself but also to gain insight into the underlying changes in Na þ reabsorption in the distal nephron.…”
Section: Introductionmentioning
confidence: 99%